Hyalinizing clear cell adenocarcinoma of the oropharynx. Issue 6 (2nd February 2012) - Adil, Eelam; Setabutr, Dhave; Mikesell, Kael; Goldenberg, David; Andersen, Peter
Abstract Background Hyalinizing clear cell adenocarcinoma (HCCA) is a rare salivary gland malignancy. To our knowledge, there are no published reports of primary clear cell carcinoma of the vallecula. Methods A 59‐year‐old man with progressive dysphagia and otalgia underwent direct laryngoscopy with biopsy of a vallecular mass. The pathology results returned as clear cell adenocarcinoma. He underwent a wide local excision for his T2N0M0 stage II tumor. Results Clear cell adenocarcinoma of the oropharynx typically presents as a painless neck mass and it can be difficult to distinguish from other clear cell malignancies. Conclusion Immunohistochemical staining is essential for narrowing the differential diagnosis of these lesions. Treatment is controversial but usually consists of wide local excision and possibly a neck dissection. © 2012 Wiley Periodicals, Inc. Head Neck, 2012